Determination of Residues of Organophosphorus Pesticides in Tobaccos by Gas Chromatography - Cai, Jibao; Zhu, Xiaolan; Gu, Xungang; Gao, Yun; Yang, Jun; Su, Qingde (Asian Journal of Chemistry, 2016)
An optimized capillary gas chromatography (GC) method was developed to determine residues of 9 organophosphorus pesticides (OPPs) in tobaccos. The 9 OPPs were extracted by acetonitrile, cleaned-up by solid-phase extraction (SPE) column. The chromatographic separation was achieved using SE-54 capillary GC column and nitrogen phosphorus detection (NPD). The result indicated that trichlorfon, dimethoate, acephate, pyrifos, dichlorvos, methyl-parathion, methamidophos, malathion and isocarbophos were isolated well within 22 min. The standard curves for 9 OPPs showed linearity (r > 0.99) over the concentration range from 20 to 1000 μg·mL–1. The precision of 9 OPPs assay expressed as the relative standard deviation (RSD), were from 1.32 to 12.20% by five parallel determinations for the same sample. The recoveries of 9 OPPs were from 76.7 to 99.6%. The detection limit of the residues of OPPs in tobaccos was achieved at 0.01 μg.g–1 levels by the proposed method. Optimisation of different chromatographic separation conditions and clean-up procedures were investigated. The validity of the method was checked by applying the standard addition technique. The method was found to be specific with good linearity, accuracy, precision and well-suited for determination of residues of OPPs in tobaccos.